Library legislation and free access to information as new topics in library and information science education. (Information Research: An International Electronic Journal)
An outline of LIS programs offered by the Department of Information Sciences, Faculty of Philosophy, University of Zagreb is given. Factors affecting the recent curriculum revision are described and the reasons for the introduction of a new course in library legislation and standards have been pointed out. The intention of the course has been to make students aware of the existence of international documents relevant to libraries and librarians and to show how the current trends are reflected in national legislation. It is hoped that the course might help students improve their understanding of the legal context surrounding libraries and other information institutions and teach them to appreciate the importance of good legislation.